Karakterisasi Asap Cair Hasil Pirolisis Sampah Plastik Kemasan Minyak Goreng Jenis PET dan Other Sebagai Bahan Bakar Alternatif - Massie, Meisye; Anom, I Dewe K; Tani, Dj.; Solikhin, Febrian (Acta Chimica Asiana, 2023)
Characterization of liquid smoke from the pyrolysis of PET and OTHER plastic packaging waste as an alternative fuel has been carried out. The pyrolysis method produces liquid smoke from PET and OTHER plastic waste at high temperatures. Pyrolysis of PET-type cooking oil packaging plastic waste produces 77.70% liquid smoke, while OTHER type of plastic packaging plastic waste pyrolysis produces approximately 71.65% liquid smoke. The physical properties of liquid smoke resulting from pyrolysis from PET and OTHER plastic cooking oil packaging waste cannot be used directly as fuel oil because some of these physical properties need to meet the SNI fuel quality standards. Identification with GC-MS that liquid smoke from PET-type plastic waste consists of 50 chemical compounds and liquid smoke from OTHER type plastic waste consists of 49 chemical compounds, composed of chemical derivatives of alkanes, alkenes, cycloalkanes, cycloalkenes, and alcohols.